Steamed water engineering mechanically robust graphene films for high-performance electrochemical capacitive energy storage. (August 2016) - Zhang, Liling; Yang, Chao; Hu, Nantao; Yang, Zhi; Wei, Hao; Chen, Changxin; Wei, Liangming; Xu, Zhichuan J.; Zhang, Yafei
Abstract: Developing versatile methods to fabricate flexible graphene film electrodes with favorable mechanical strength and desirably tailored areal and volumetric capacitances are very challenging for high-performance capacitive energy storages. Here, we present a simple yet versatile method to regulate the structures of scalable free-standing reduced graphene oxide (rGO) films for high-performance flexible supercapacitors. Steamed water with a high pressure and a moderately high temperature in closed vessels was used to prepare reduced graphene oxide with regulated structures, and the resultant rGO films exhibited favorable mechanical robustness (with modulus and tensile strength higher than 0.28 GPa and 5.9 MPa respectively) as well as excellently controllable areal and volumetric capacitances (with a highest gravimetric specific capacitance, a highest areal specific capacitance, and a highest volumetric capacitance up to 340 F/g, 915 mF/cm 2, and 326 F/cm 3, respectively), revealing the versatile behavior of this regulation technique for high-performance flexible energy storage. In addition, a typical assembled all-solid-state supercapacitor based on as-fabricated graphene films shows large gravimetric and areal specific capacitances, high energy density and power density, as well as excellent capacitance stability, highlighting its great potential for high-performance flexible energy storage devices. Graphical abstract: This work demonstrates a simple yet versatile method to regulate the structures of scalable free-standing reduced graphene oxide (rGO) films for high-performance flexible supercapacitors. Steamed water with a high pressure and a moderately high temperature in closed vessels was used to prepare rGO films with regulated structures, and the resultant rGO films exhibited favorable mechanical robustness as well as excellently controllable areal and volumetric capacitances, revealing the versatile behavior of this fabrication method for high-performance flexible energy storage. Highlights: Engineering graphene films was achieved by steamed water regulation techniques. Gravimetric specific capacitance of tailored graphene films can reach 340 F/g. A highest specific capacitance of 326 F/cm 3 or 915 mF/cm 2 can be achieved. Assembly of high-performance flexible solid-state supercapacitor was achieved.